Fifty Years of 3He-Rich Events - Reames, Donald V. (Frontiers in Astronomy and Space Sciences, 2021)
The early 1970s saw a new and surprising feature in the composition of solar energetic particles (SEPs), resonant enhancements up to 10,000-fold in the ratio 3He/4He that could even make 3He dominant over H in rare events. It was soon learned that these events also had enhancements in the abundances of heavier elements, such as a factor of ~10 enhancements in Fe/O, which was later seen to be part of a smooth increase in enhancements vs. mass-to-charge ratio A/Q from H to Pb rising by a factor of ~1000. These events were also associated with streaming 10 – 100 keV electrons that produce type III radio bursts. In recent years we have found these “impulsive” SEP events to be accelerated in islands of magnetic reconnection from plasma temperatures of 2 – 3 MK on open field lines in solar jets. Similar reconnection on closed loops traps the energy of the particles to produce hot (>10 MK), bright flares. Sometimes impulsive SEP intensities are boosted by shock waves when the jets launch fast coronal mass ejections. No single theory yet explains both the sharp resonance in 3He and the smooth increase up to heavier elements; two processes seem to occur. Sometimes the efficient acceleration even exhausts the rare 3He in the source region, limiting its fluence.